Health literacy in nursing : providing person-centered care - Parnell, Terri Ann (Springer Publishing, 2014)
""Dr. Parnell has captured the essence of health literacy and cultural competence, not only for nurses, but also applicable to all care providers and community workers . [and] provides us with a road map to enhance our success through health literacy and cultural competence. This is a must read for all health professionals.""--Richard H. Carmona, MD, MPH, FACS (From the Foreword). 17th Surgeon General of the United States (2002-2006). Distinguished Professor, University of Arizona. Promoting the health literacy of patients across all settings is an essential component of prevention, wellness